Water Issues in Florida: How Extension Can Facilitate Stakeholder Engagement and Involvement - Erica Odera; Alexa Lamm; Michael Dukes; Tracy Irani; Hannah Carter (EDIS, 2013)
This 6-page fact sheet is a brief description of recent discussions and policies surrounding water management, use, and quality in Florida. The goal of this publication is to provide brief, but clear, information about the trends in policies that can be used by Extension agents to increase educated conversations about water issues. Water in Florida is a contested issue, and Extension agents may be called upon as a source of unbiased information by the public. Having an understanding of important agricultural and natural resources issues in Florida, including water, can help facilitate conversation, raise awareness, and lead to informed decision making. Written by Erica Odera, Alexa Lamm, Michael Dukes, Tracy Irani, and Hannah Carter, and published by the UF Department of Agricultural Education and Communication, December 2013. http://edis.ifas.ufl.edu/wc151